Recent Progress of Copper-Based Nanomaterials in Tumor-Targeted Photothermal Therapy/Photodynamic Therapy - Xiqian Zhuo; Zhongshan Liu; Reyida Aishajiang; Tiejun Wang; Duo Yu (Pharmaceutics, 2023)
Nanotechnology, an emerging and promising therapeutic tool, may improve the effectiveness of phototherapy (PT) in antitumor therapy because of the development of nanomaterials (NMs) with light-absorbing properties. The tumor-targeted PTs, such as photothermal therapy (PTT) and photodynamic therapy (PDT), transform light energy into heat and produce reactive oxygen species (ROS) that accumulate at the tumor site. The increase in ROS levels induces oxidative stress (OS) during carcinogenesis and disease development. Because of the localized surface plasmon resonance (LSPR) feature of copper (Cu), a vital trace element in the human body, Cu-based NMs can exhibit good near-infrared (NIR) absorption and excellent photothermal properties. In the tumor microenvironment (TME), Cu2+ combines with H2O2 to produce O2 that is reduced to Cu1+ by glutathione (GSH), causing a Fenton-like reaction that reduces tumor hypoxia and simultaneously generates ROS to eliminate tumor cells in conjunction with PTT/PDT. Compared with other therapeutic modalities, PTT/PDT can precisely target tumor location to kill tumor cells. Moreover, multiple treatment modalities can be combined with PTT/PDT to treat a tumor using Cu-based NMs. Herein, we reviewed and briefly summarized the mechanisms of actions of tumor-targeted PTT/PDT and the role of Cu, generated from Cu-based NMs, in PTs. Furthermore, we described the Cu-based NMs used in PTT/PDT applications.